ON THE ROLE OF "ALTERNATIVE PRACTICES AND THERAPIES" COURSE IN BSC NURSING PROGRAMS: MEETING DIFFERENT EDUCATIONAL PERSPECTIVES ON THE SCIENTIFIC PRODUCTION IN HEALTHCARE (Fiep Bulletin - online, 2014)
Controversies around Complementary and Integrated Practices (Práticas Integrativas e Complementares) have become more pronounced in the context of undergraduate (Bachelor) courses in Nursing, based on the COFEN 197/97 regulation, which defines and classifies such practices as of high-relevance for the Nursing practitioner. Therefore, it is essential to understand how these undergraduate programs include the referred course in the educational program to be followed by the future practitioners from this field. Hence, the goal of this research has been to assess how the corresponding course has been provided in the context of undergraduate courses in Nursing. Such a study has been based on an integrated research on papers available online at the Healthcare Virtual Library (Biblioteca Virtual em Saúde - BVS). The keywords used follow: "Complementary Practices", "Nursing", "Graduation", "Teaching". This search has returned 19 (nineteen) results, among which 07 (seven) have been referred to as especially referred to the main research question of this study. Therefore, this study has indicated some critical limitations on how the referred course have been taught in different (undergraduate) educational programs in Nursing, despite available regulations supporting this knowledge field. More specifically, it has been noticed that there is no consensus about the main topics included in the corresponding course countrywide. Hence this may trigger possible controversies on the display and apprehension of the main topics of the course, which represents potentially a problem of internal consistency in the educational program of the future Nursing practitioner. Thus, a collective effort is necessary (involving the universities providing the referred course) towards the definition of a proposal for integrating and structuring the body of knowledge of the referred undergraduate course.
Keywords: Complementary and Integrated Practices; Nursing Educational Program; Healthcare Education